2013
DOI: 10.2147/dddt.s37512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 7-Difluoromethyl-5, 4΄-dimethoxygenistein on aorta atherosclerosis in hyperlipidemia ApoE-/- mice induced by a cholesterol-rich diet

Abstract: Purpose7-Difluoromethyl–5, 4′-dimethoxygenistein (DFMG), prepared by the difluoromethylation and alkylation of Genistein, is an active new chemical entity. Its anti-atherosclerosis effect was found in a series of studies in vitro. In this article, we explored and evaluated the anti-atherosclerosis effect via its protection of endothelial function in ApoE−/− mice that were fed a high-fat diet.MethodsFive C57BL/6J mice were selected as a control group and were fed a 1% high-fat diet (control group, n = 5). Five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
3
8
0
Order By: Relevance
“…HCD feeding showed significant elevation of TC, LDL, and TG, which increase lipid peroxidation and influence the development of atherosclerosis, in agreement with several studies [ 12 ]. In contrast, a significant decrease noted in serum HDL in hypercholesterolemic rabbits was also reported by Ismail et al [ 4 ].…”
Section: Discussionsupporting
confidence: 91%
“…HCD feeding showed significant elevation of TC, LDL, and TG, which increase lipid peroxidation and influence the development of atherosclerosis, in agreement with several studies [ 12 ]. In contrast, a significant decrease noted in serum HDL in hypercholesterolemic rabbits was also reported by Ismail et al [ 4 ].…”
Section: Discussionsupporting
confidence: 91%
“…These results support the findings of previous studies, which reported that HCD increased MDA level but decreased the activity of SOD level [31,32]. HCD-feeding causes oxidative stress by increasing the production of reactive oxygen species (ROS), mediated lipoprotein oxidation, particularly LDL particles that cause lipid peroxidation and subsequent influence the development of atherosclerosis [33]. Lipid peroxidation plays an important role in the pathophysiology of atherosclerosis so a decrease in lipid peroxidation leads to a reduction of hypercholesterolemia-induced atherosclerosis [34].…”
Section: Dmf Effects On Serum Lipid Profile Of Hypercholesterolemic Rsupporting
confidence: 92%
“…The authors of the present study, also previously reported that DFMG could protect VECs through inhibition of the mitochondrial apoptotic pathway ( 24 , 25 ). Furthermore, the preventive effect of DFMG was more apparent compared with the therapeutic effect within apolipoprotein E −/− mice induced by a cholesterol-rich diet ( 26 ).…”
Section: Introductionmentioning
confidence: 99%